Assessment of in vitro anti-skin aging activities of Phyllanthus indofischeri Bennet extracts for dermatological and aesthetic applications - Boonpisuttinant, Korawinwich; Taka, Thanachai; Ruksiriwanich, Warintorn; Chutoprapat, Romchat; Udompong, Sarinporn; Kansawang, Rattiya; Sangsee, Jinapa; Chompoo, Wirinda; Samothai, Kitrawi; Srisuttee, Ratakorn (My University, 2023)
Giant Indian Gooseberry (GIG) or Phyllanthus indofischeri Bennet are commercially cultivated and commonly used herbs in Traditional medicine, especially in Thailand. The aim of this study was to assess the potential of the GIG extracts in anti-aging activities to be a dermatological application. The juice, meat residues, and seeds of GIG collected from Sra Kaeo Province, Thailand, were extracted by the Boiling method (B) and the Maceration process (M) by using 95% ethanol as a solvent. The GIG extracts gave the total phenolic, total flavonoid contents and quercetin contents, as well as exhibited anti-oxidative activities. The GIG-R-B extract inhibited tyrosinase activity and had the highest anti-melanogenesis activity on B16F10 cells at 31.63 ± 0.70%. The GIG-S-B, GIG-S-M, and GIG-R-M extracts demonstrated the highest collagen biosynthesis, which was comparable to vitamin C (p < 0.05), whereas the GIG-R-B extracts gave the highest stimulation of anti-aging genes (SIRT1 and FOXO1). All extracts at the concentration of 0.1 mg/mL showed no cytotoxicity on human skin fibroblasts. Therefore, the GIG-S-B extract was discovered to be a promising natural anti-aging agent for dermatological health and aesthetic applications that can be further developed in cosmetic, functional food and food supplement industries.